FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN WHOLESALE AND RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Carrolina Rahardjo; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study sought to examine the effect of profitability terhadapm capital structure, the company's growing influence on the capital structure, asset structure pengarub against modaol structure and the effect of firm size on the capital structure.The sample in this study is a wholesale and retail company, amounting to 75 companies.The results showed that there was a negative effect of profitability on the capital structure there is no influence sales growth on the capital structure there is a positive effect on the capital structure asset structure, there is the influence of the size of the company on the capital structure